T-cell receptor activator of nuclear factor-κB ligand/osteoprotegerin imbalance is associated with HIV-induced bone loss in patients with higher CD4+ T-cell counts. (24th April 2018) - Titanji, Kehmia; Vunnava, Aswani; Foster, Antonina; Sheth, Anandi N.; Lennox, Jeffrey L.; Knezevic, Andrea; Shenvi, Neeta; Easley, Kirk A.; Ofotokun, Ighovwerha; Weitzmann, M. Neale
Abstract : Objective: Higher incidence of osteopenia and osteoporosis underlie increased rates of fragility fracture in HIV infection. B cells are a major source of osteoprotegerin (OPG), an inhibitor of the key osteoclastogenic cytokine receptor activator of nuclear factor-κB ligand (RANKL). We previously showed that higher B-cell RANKL/OPG ratio contributes to HIV-induced bone loss. T-cell OPG production in humans, however, remains undefined and the contribution of T-cell OPG and RANKL to HIV-induced bone loss has not been explored. Design: We investigated T-cell OPG and RANKL production in ART-naive HIV-infected and uninfected individuals in relation to indices of bone loss in a cross-sectional study. Methods: T-cell RANKL and OPG production was determined by intracellular staining and flow cytometry, and plasma levels of bone resorption markers were determined by ELISA. Results: We demonstrate for the first time in-vivo human T-cell OPG production, which was significantly lower in HIV-infected individuals and was coupled with moderately higher T-cell RANKL production, resulting in a significantly higher T-cell RANKL/OPG ratio. T-cell RANKL/OPG ratio correlated significantly with BMD-derived z -scores at the hip, lumbar spine and femur neck in HIV-infected individuals with CD4 + T-cell counts at least 200 cells/μl but not in those with lower counts. Conclusion: Our data suggest that T cells may be a physiologically relevant source of OPG and T-cell RANKL/OPG imbalance is associated with HIV-induced bone loss in CD4 + T-cell-sufficient patients. Both B and T lymphocytes may thus contribute to HIV-induced bone loss. Abstract : Supplemental Digital Content is available in the text